The Association Between Uric Acid and Symmetric Dimethylarginine Levels in Patients Undergoing Continuous Ambulatory Peritoneal Dialysis - Rizki Yaruntradhani Pradwipa; Ni Made Hustrini; Rudy Hidayat; Hamzah Shatri (Acta Medica Indonesiana, 2022)
Background: Uric acid (UA) levels are associated with increased risk of cardiovascular events and mortality in hemodialysis (HD) and continuous ambulatory peritoneal dialysis (CAPD) patients. In a study with a population of healthy young adults and HD there was a correlation between high blood uric acid levels and blood symmetric dimethylarginine (SDMA) level. However, in CAPD population, there are still conflicting data on the mechanism of increased risks related to uric acid levels. This study aimed to assess the association between uric acid levels and SDMA in the subjects undergoing CAPD. Methods: This was a cross – sectional study conducted in all the adults who underwent CAPD for at least three months in tertiary hospital in Jakarta, Indonesia. Subjects already on uric lowering therapy, pregnant or lactating women, and those with a history of malignancy were excluded. Uric acid and SDMA level were measured at the same time patients controlled to outpatient clinic. Bivariate analysis was performed using the Mann – Whitney test and multivariate analysis performed using logistic regression test. Results: A total of 55 subjects were included. The median level of UA was 7.30 + 1.59 mg/dl and 33 subjects (60%) had UA levels of 7 mg/dl or higher. The median SDMA level was 633.73 + 231.54 ng/mL. Subjects with UA levels > 7 mg/dl had significantly higher SDMA levels compared to subjects with UA levels < 7 mg/dl (721.58 + 220.57 vs 501.95 + 182; P < 0.001). The cut – off value of SDMA 536 ng/mL was obtained from the receiver operating characteristic (ROC) curve with sensitivity 81.8%, specificity 63.6%, PPV 77.78% and NPV 73.68%. After fully adjusted with the confounders, the determinant factors in this study were diabetes mellitus (OR: 7.844; CI95%: 1.899 – 32.395: P value: 0.004) and dyslipidemia (OR: 6.440; CI95%: 1.483 – 27.970; P value: 0.013) as risk factors. Conclusion: In CAPD patients, UA levels above 7 mg/dl were associated with increased SDMA levels. This study demonstrates the determinant factors regarding association between UA level and SDMA in CAPD patients were diabetes mellitus and dyslipidemia. The cut – off value of SDMA above 536 ng/mL were significant to increased risk of cardiovascular events.